A New Year's Present from a Mathematician - Lawrence, Snezana (Milton : CRC Press LLC, 2019)
A New Year's Present from a Mathematician is an exciting book dedicated to two questions: What is it that mathematicians do? And who gets to be called a mathematician' and why? This book seeks to answer these questions through a series of stories ranging from the beginning of modern mathematics through to the 20th century, but not in a usual, chronological manner. The author weaves her story around major questions concerning nature of mathematics, and links mathematicians by the substance of their ideas and the historical and personal context in which they were developed. Ideal as a gift for anyone with an interest in mathematics, this book gives a powerful insight into mathematical concepts in an easy-to-read-and-digest manner, without trivializing their nature. The attention given to engaging examples, framed within a poetic narrative structure, means that this book can be enjoyed by almost anyone, regardless of their level of mathematical education.
The Legacy for the FutureNotes; Chapter 12 December; What Can a Mathematician Give to Their Friend as a New Year's Present?; The Journey to Prague; The Witches and Dreams; Friendships that Last Centuries; Let's Pack our Present Neatly; Notes; Final Remarks; Bibliography; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: MATHEMATICS / General; MATHEMATICS / Applied; MATHEMATICS / History & Philosophy; Mathematics -- History; Mathematicians -- History